2022
DOI: 10.1128/spectrum.02290-21
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter Genomic Analysis of Carbapenem-Resistant Klebsiella pneumoniae from Bacteremia in China

Abstract: K. pneumoniae is one of the most frequent Gram-negative bacilli isolated from bloodstream infections worldwide and recent studies have shown an increased rate of carbapenem resistance in China. Among carbapenem-resistant K. pneumoniae (CRKP) diverse clones have been reported, especially the high-risk clone ST11, which also exhibited a multidrug resistant phenotype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
20
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 49 publications
1
20
1
Order By: Relevance
“… 30 Another study reported that genes encoding yersiniabactin were identified in 83.7% (123/147) of the CRKP isolates. 31 Sherif et al found that yersiniabactin was the most common virulence factor (69.2%) in 39 randomly selected, geographically diverse MDR Kp isolates. 32 Furthermore, aerobactin was the dominant siderophore produced by the hvKp strains and the critical siderophore that enhances virulence ex vivo and in vivo.…”
Section: Discussionmentioning
confidence: 99%
“… 30 Another study reported that genes encoding yersiniabactin were identified in 83.7% (123/147) of the CRKP isolates. 31 Sherif et al found that yersiniabactin was the most common virulence factor (69.2%) in 39 randomly selected, geographically diverse MDR Kp isolates. 32 Furthermore, aerobactin was the dominant siderophore produced by the hvKp strains and the critical siderophore that enhances virulence ex vivo and in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…For virulence factors, we found that ST15 CRKP carried genes encoding aerobactin, enterobactin, and yersiniabactin, including iutA, ybt, irp1, irp2, fyuA, ent, fepA , that are essential for bacterial growth. According to previous studies, siderophores systems, such as aerobactin, yersiniabactin, and enterobactin, are more common in invasive isolates than in non-invasive isolates [ 38 ]. Although yersiniabactin was detected in nearly 30% of the non-invasive isolates and almost 80% of the bacteraemia isolates, we detected it in 100% of the ST15 CRKP.…”
Section: Discussionmentioning
confidence: 99%
“…Currently K. pneumoniae is the most common cause of nosocomial infections in Russia, accounting for almost 30% of cases in 2020 according to the AMRmap database [ 20 ] ( , accessed on 23 August 2022). The isolates studied belonged to the ST395 group, which is known as a high-risk clone with high capacity of drug resistance acquisition [ 21 ] and was revealed in different countries, for example, in France [ 22 ], Hungary [ 23 ] and China [ 24 ]. Additionally, ST395/KL39 isolates carrying the blaOXA-48 gene were recently revealed in Russia, including CriePir234 (GCA_009661195.1) described earlier by us [ 25 ], as well as in Finland in the same year, and were also obtained in 2013–2016 in such distant regions of the world as China, Germany and the USA.…”
Section: Discussionmentioning
confidence: 99%